Poliovirus seroprevalence before and after interruption of poliovirus transmission in Kano State, Nigeria. Issue 42 (30th September 2016) - Iliyasu, Zubairu; Verma, Harish; Craig, Kehinde T.; Nwaze, Eric; Ahmad-Shehu, Amina; Jibir, Binta Wudil; Gwarzo, Garba Dayyabu; Gajida, Auwalu U.; Weldon, William C.; Steven Oberste, M.; Takane, Marina; Mkanda, Pascal; et al.
Highlights: Polio seroprevalence surveys help measure progress towards polio eradication. Nigeria program conducted multiple seroprevalence surveys in northern states. This article covers seroprevalence survey in Kano Nigeria in 2013 and 2014. Data represents levels before and after the interruption of poliovirus transmission. Significant improvement in seroprevalence in 2014 over 2013, but gaps continue. Good participation even by vaccine refusers in this health facility based project. Abstract: Introduction: In September 2015, Nigeria was removed from the list of polio-endemic countries after more than 12 months had passed since the detection of last wild poliovirus case in the country on 24 July 2014. We are presenting here a report of two polio seroprevalence surveys conducted in September 2013 and October 2014, respectively, in the Kano state of northern Nigeria. Methods: Health facility based seroprevalence surveys were undertaken at Murtala Mohammad Specialist Hospital, Kano. Parents or guardians of children aged 6–9 months, 36–47 months, 5–9 years and 10–14 years in 2013 and 6–9 months and 19–22 months (corresponding to 6–9 months range at the time of 2013 survey) in 2014 presenting to the outpatient department, were approached for participation, screened for eligibility and asked to provide informed consent. A questionnaire was administered and a blood sample collected for polio neutralization assay. Results: Among subjects aged 6–9 months in the 2013 survey, seroprevalence was 58% (95% confidence interval [CI] 51–66%) to poliovirus type 1, 42% (95% CI 34–50%) to poliovirus type 2, and 52% (95% CI 44–60%) to poliovirus type 3. Among children 36–47 months and older, seroprevalence was 85% or higher for all three serotypes. In 2014, seroprevalence in 6–9 month infants was 72% (95% CI 65–79%) for type 1, 59% (95% CI 52–66%) for type 2, and 65% (95% CI 57–72%) for type 3 and in 19–22 months, 80% (95% CI 74–85%), 57% (49–63%) and 78% (71–83%) respectively. Seroprevalence was positively associated with history of increasing oral poliovirus vaccine doses. Conclusions: There was significant improvement in seroprevalence in 2014 over the 2013 levels indicating a positive impact of recent programmatic interventions. However the continued low seroprevalence in 6–9 month age is a concern and calls for improved immunization efforts to sustain the polio-free Nigeria.